Alpine ice-core drilling in the North Pacific region. Issue 68 (2014) - Matoba, Sumito; Shimbori, Kunio; Shiraiwa, Takayuki
Abstract: The Institute of Low Temperature Science at Hokkaido University conducted ice-core drilling in alpine glaciers in the northern North Pacific region to reconstruct climate change in this region for the past few hundred years. We drilled two ice cores in the Kamchatka Peninsula, Russia. An ice core with a length of 211 m was drilled on a glacier at the summit caldera of Ushkovsky mountain in 1998. A second core, with a length of 115m (until bedrock was reached), was drilled on a glacier at the summit caldera of Ichinsky mountain in 2006. We drilled three further ice cores in Alaska, USA. Two ice cores with lengths of 50 and 212m were drilled on a glacier at the summit caldera of Mount Wrangell in 2003 and 2004. The third ice core was drilled on the ice divide among three glaciers, Black Rapids, Trident and Susitna glaciers, which represent a flat saddle north of Aurora Peak in the Alaska Range. This paper details the field operations and characteristics of the different ice-drilling systems used and the problems encountered.